Education policy : philosophical critique - Smith, Richard (Richard D.) (Chichester, West Sussex, UK ; Malden, MA : Wiley, 2013)
Education Policy sees 12 philosophers of education critique current and recent UK educational policies relating to higher education and faith-based education, assessment, the teaching of reading, vocational and civic education, teacher education, the influence of Europe and the idea of the 'Big Society'. Twelve philosophers of education subject elements of current and recent UK educational policy to critique. Forthright and critical, the contributors are unafraid to challenge current orthodoxies. Offers thought-provoking insights into modern education policy.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Education and state -- Philosophy; Education and state -- Philosophy; EDUCATION -- Administration -- General; EDUCATION -- Educational Policy & Reform -- General; Education and state -- Philosophy; Electronic books; Electronic books